The significance of dominant ball carrying collisions as an indicator of success in rugby union and the biomechanical analysis thereof - Kruger, P.E. (Pieter Ernst) (University of Pretoria, 2013)
Thesis (DPhil (Human Movement Science))--University of Pretoria, 2006.